2019
DOI: 10.1039/c8ra10509j
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic decomposition of N2O over Cu–Al–Ox mixed metal oxides

Abstract: Cu–Al–Ox mixed metal oxides with intended molar ratios of Cu/Al = 85/15, 78/22, 75/25, 60/30, were prepared by thermal decomposition of precursors at 600 °C and tested for the decomposition of nitrous oxide (deN2O).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Influence of Nd addition on the reducibility of the materials can be visualized by the change of the shape of H 2 ‐TPR profiles and H 2 consumption. Cu 0.8 Al 0.2 showed a broad peak in range from 200–400 °C, associated to the reduction of copper oxide to metallic copper . In fact, its hydrogen consumption was 10.3 mmol g −1 , almost the same as expected amount (Table ).…”
Section: Resultssupporting
confidence: 64%
“…Influence of Nd addition on the reducibility of the materials can be visualized by the change of the shape of H 2 ‐TPR profiles and H 2 consumption. Cu 0.8 Al 0.2 showed a broad peak in range from 200–400 °C, associated to the reduction of copper oxide to metallic copper . In fact, its hydrogen consumption was 10.3 mmol g −1 , almost the same as expected amount (Table ).…”
Section: Resultssupporting
confidence: 64%
“…The hydrogen consumption of both CuAl and CuO started around 130°C but the reduction of copper oxide to metallic copper was completed at 350°C on CuO and 400°C on CuAl, despite the lower amount of CuO present in the latter sample (Fig. 4A) [47]. This effect is similar to the delayed reduction of CuO when deposited in a limited amount on c-Al 2 O 3 support, the lower reducibility being attributed to strong oxide-support interaction [48].…”
Section: H 2 -Tpr Of Catalysts and Benchmark Materialsmentioning
confidence: 82%
“…30,31 Because of the potentially harmful effects of nitrous oxide on the global environment, urgent control and reduction of the emission has been required. Its catalytic decomposition into nitrogen and oxygen is considered the most effective and economic one, and various supported [32][33][34][35][36] and mixed oxide [37][38][39][40][41] catalysts have been developed. We previously indicated that copper supported silica-alumina hollow sphere particles were highly active for the decomposition reaction.…”
Section: Introductionmentioning
confidence: 99%